(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
The purpose of this work is to study the global stability of specific nonlinear parabolic equations incorporating the p-Laplacian operator, with a primary emphasis on their application in biology, particularly in the context of epidemiology. This investigation entails the construction of Lyapunov functions derived from the associated ODEs. To elucidate our approach, we provide an illustrative example from the field of epidemiology.